Contribution to the study of angiographic semiology of the thyroid - Gary, Ruben; Acosta Ferreira, Walter; Ravera, Juan J; Tenyi, Andrés; Azambuja, Néstor (Cirugía del Uruguay, 2021)
We have 40 observations made through infraclavicular puncture of the subclavian artery and through a Seldinger catheter and selective technique which is a contribution of angiographic semiology to the study of the thyroid gland. It is accompanied by a general analysis of the vascular trunks, thyroid pedicles and intraparenchimatose circulation. Character·stic aspects of difuse goiter are established: an image of well defined uniform opacity, with intense capture of the contrast by the arteriolo-capillarybed. Nodular goiter, shows a complex radiological morphology: its most frequent signs are irregular impregnation images and vascular tracings which outline displacement structures. Thyroid atrophy in mixedema is expressed by the small calibre of its pedicles and limited thyroid vascularization. The author concludes that angiography supplies important data on various aspects: diagnosis of the anatomo-clinical variety of goiter; morphological elements of interest in the planning of surgery; functional elements deduced by the angiographic profile of the gland; elements which appear in the ,comparison of the angiogram with other exploratory means: gammagram, histopathology, etc.; exploration of the residual stump and postoperatory recurrency.